2011
DOI: 10.1177/0148607111414713
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Catheter Thrombosis Associated With 70% Ethanol Locks in Pediatric Intestinal Failure Patients on Home Parenteral Nutrition

Abstract: Central venous catheter (CVC) ethanol locks may reduce catheter-related bloodstream infection (CRBSI). Four children with intestinal failure on home parenteral nutrition (HPN) were selected for 70% ethanol locks because of their high rate of CRBSI. The 70% ethanol locks were instilled at a volume equal to the estimated internal volume of the CVC. Two children (aged 4 and 11 years) received 70% ethanol locks as CRBSI prophylaxis; another 2 children (aged 10 and 11 years) received 70% ethanol locks as adjunctive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 16 publications
1
31
2
1
Order By: Relevance
“…In pediatric patients on total parenteral nutrition a standardized procedure to minimize systemic effects revealed difficulties in withdrawing ELs (70–100%), as well as vascular access occlusion or visible line thrombosis. [25], [26], [28], [50] The vast majority of studies suggest flushing ELs at the end of dwell time to prevent clotting inside the catheter, most likely because ethanol is considered to resolve lipid residues in CVCs used for total parenteral nutrition, although the underlying rationale was not given. [12], [27], [39], [43], [51][55] Introduction of irreversibly precipitated protein particles into the systemic circulation might occur not only when the ethanol lock solution is injected as a bolus, but also following every single instillation of ethanol due to gravity induced leakage of precipitate, thus indicating physical incompatibility of high ethanol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients on total parenteral nutrition a standardized procedure to minimize systemic effects revealed difficulties in withdrawing ELs (70–100%), as well as vascular access occlusion or visible line thrombosis. [25], [26], [28], [50] The vast majority of studies suggest flushing ELs at the end of dwell time to prevent clotting inside the catheter, most likely because ethanol is considered to resolve lipid residues in CVCs used for total parenteral nutrition, although the underlying rationale was not given. [12], [27], [39], [43], [51][55] Introduction of irreversibly precipitated protein particles into the systemic circulation might occur not only when the ethanol lock solution is injected as a bolus, but also following every single instillation of ethanol due to gravity induced leakage of precipitate, thus indicating physical incompatibility of high ethanol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Y, aunque no hay evidencia de que esa precipitación sea clínicamente relevante, se desaconseja su uso combinado. Hay varios casos publicados, sobre todo de oclusión del catéter, en relación con el uso de etanol (42,43). Sin embargo, también es cierto que existen otros 15 estudios publicados en los que no se refiere mayor tasa de disfunción u oclusión del catéter en el grupo de etanol.…”
Section: Etanolunclassified
“…Kayton et al had 3 out of 12 patients develop catheter thrombosis while using daily ethanol locks for 12 h at a time (Kayton et al 2010), and Mouw et al reported 1 out of 10 children developing catheter thrombosis when using ethanol locks daily for 4-14 h (Mouw et al 2008). A recently published case series noted that clot developed in the CVCs of 4 patients managed with ethanol lock anywhere from 3 to over 400 days after starting the lock therapy (Wong et al 2012). In our own retrospective review of 10 children with intestinal failure treated daily with 70 % ethanol lock for at least 4 h at a time, there were 2 patients who developed catheter thrombosis (Wales et al 2011).…”
Section: Safety Of Ethanol Locksmentioning
confidence: 99%